Catholicism and crisis in modern France : French Catholic groups at the threshold of the Fifth Republic - Bosworth, William (Princeton legacy library., 1962)
The author discusses the role of French Catholicism in the internal and foreign affairs of modern France, with a detailed examination of French Catholic groups and their effect on temporal life. Presenting a wealth of material from official archives and files of French Catholic periodicals and organizations, Mr. Bosworth supplements his research by direct interviews with key personnel from a variety of Catholic groups. Originally published in 1961. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.